2010
DOI: 10.1108/00070701011018824
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of food purchasing behaviour of consumers from supermarkets

Abstract: Purpose -This study was conducted with the aim of determining the food purchasing behaviour of consumers from supermarkets. Design/methodology/approach -A total of 430 consumers, 194 males and 236 females, with an average age of 29.96^10.99 were included in this study, and was conducted to find out the criteria which consumers took into account while purchasing food. Findings -A significant relationship was determined between the scores the consumers received from nutrition, the reliability and all of the shop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 23 publications
(29 reference statements)
3
39
2
Order By: Relevance
“…Consumers evaluate various dimensions of food products to make their purchase decision. Nevin and Suzan Seren (2010) reveal that Turkish consumers are concerned about food nutrition and safety when shopping at supermarket. Spinks and Bose (2002), in a study of seafood purchasing in New Zealand, find that consumer decision is influenced by product characteristics of nutrition, taste, health benefit and ease of preparation.…”
Section: Productmentioning
confidence: 99%
See 3 more Smart Citations
“…Consumers evaluate various dimensions of food products to make their purchase decision. Nevin and Suzan Seren (2010) reveal that Turkish consumers are concerned about food nutrition and safety when shopping at supermarket. Spinks and Bose (2002), in a study of seafood purchasing in New Zealand, find that consumer decision is influenced by product characteristics of nutrition, taste, health benefit and ease of preparation.…”
Section: Productmentioning
confidence: 99%
“…French (2003) indicates that food pricing is an essential factor that shapes individual choice. Given the importance of cost saving consumers evaluate and compare price during the process of food purchasing (Nevin & Suzan Seren, 2010). Conventional wisdom indicates that, a high retail price which reflects immediate monetary costs are likely to hinder consumer purchase behavior while a low price or competitive price leads to an increase in store traffic and product sales (Barbara, Lois, & Bobby, 1996;Pan & Zinkhan, 2006).…”
Section: Productmentioning
confidence: 99%
See 2 more Smart Citations
“…This result was interesting, indicating that earlier campaign efforts of promoting consumption of leafy AIVs in urban areas were not in vain. Perhaps this is because better-educated households are more likely to attain dietary information on nutritious and healthier food items like indigenous vegetables (Sanlier and Karakus 2010;Gido et al 2017). Contrary to findings in this study, Gido et al (2017) revealed that African night shade was less likely to be accepted for consumption by more-educated urban decision-makers.…”
Section: Determinants Of Consumption Intensity Of Leafy Aivsmentioning
confidence: 99%